Antarctic distribution, pigment and lipid composition, and molecular identification of the brine dinoflagellate Polarella glacialis (Dinophyceae) - Thomson, P; Wright, SW; Bolch, CJS; Nichols, PD; Skerratt, J; McMinn, A (Journal of Phycology, 2004)
Polarella glacialis (Montresor et al.) was identified in Davis Station sea ice by morphological and DNA sequence comparison of cultures with those of the authentic strain P. glacialis CCMP 1383 isolated from McMurdo Sound. Cells and cysts of the Davis isolate (FL1B) were morphologically indistinguishable from P. glacialis, and comparison of the large subunit rDNA of both cultures demonstrated only 0.2% sequence divergence over 1366 base pairs. The photosynthetic pigments of P. glacialis (strains FL1B and CCMP 1383) were typical of dinoflagellates, with peridinin (contributing up to 31%) as the major accessory pigment. Extremely high levels of polyunsaturated fatty acids (PUFA, up to 76.3%) were characteristic of P. glacialis isolate FL1B. The high PUFA concentration of this species is thought to be an adaptation to survive the cold temperatures of the upper fast ice. The sterol profile of FL1B was atypical of dinoflagellates, with 4-desmethylsterols (up to 79%) in greater abundance than 4-methyl sterols (up to 24%). 27-Nor-24-methylcholest-5,22E-dien-3- ol was identified as the principle sterol in P. glacialis, contributing up to 64% of the total sterol composition.